2015
DOI: 10.1016/j.sbspro.2015.03.105
|View full text |Cite
|
Sign up to set email alerts
|

The Organizational Culture in Public and Private Institutions

Abstract: Every organization, regardless of region, country or sector, has a culture of its own. The organizational culture of a public institution, as opposed to the organizational culture of a private organization, is developing within a broader spiritual matrix. The objective of the case study was to identify the type of the organizational culture within two Romanian institutions, i.e. a public (Calarasi City Hall) and a private (ACTIVE TRADING SRL) one, for a comparative perspective on their organizational culture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 4 publications
(2 reference statements)
4
11
0
2
Order By: Relevance
“…The outcome of the study has been supported by other researchers in similar studies. In case of Public enterprises, it is the organizational culture that influences the sentiments, ideas, beliefs held by its employees and this influence gains strength with time (Rus and Rusu, 2015). In the healthcare sector it has been reported that, culture of comradeship acted as the antecedent for employee engagement (Barsade and O Neill, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome of the study has been supported by other researchers in similar studies. In case of Public enterprises, it is the organizational culture that influences the sentiments, ideas, beliefs held by its employees and this influence gains strength with time (Rus and Rusu, 2015). In the healthcare sector it has been reported that, culture of comradeship acted as the antecedent for employee engagement (Barsade and O Neill, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Liao et al (2013) in their study of Chinese workers have found that positive work environment among teams creates psychological safety and which in turn leads to employee engagement. Rus and Rusu (2015) have claimed that it is the organizational culture of a public sector company that influences the sentiments, ideas, beliefs held by its employees. Moreover, this influence gains strength with the passage time (ibid).…”
Section: Theoretical Groundingsmentioning
confidence: 99%
“…The University concluded that the organizational culture is the basis for quality management and is directly linked to development. Rus and Rusu (2015) examined the organizational culture in public and private organizations. To this end, a questionnaire including ten questions was applied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Özellikle politik aktörler ve örgütün yönetim yapısı, örgüt kültürü ve kamu görevlilerin davranışları üzerinde oldukça etkilidir. Ancak bir kamu örgütünün yönetim yapısı sürekli olarak değişirse orta ve uzun vadede siyasanın ve yönetimin şekillendirdiği baskın örgüt kültürü anlayışı zayıflayabilir (Allaire & Firsirotu, 1984;Balthazard et al, 2006;Deal & Kennedy, 2000;Gordon, 1991;Hofstede, 1998;Rus & Rusu, 2014;Smircich & Calas, 1987;Valle, 1999;Wallace et al, 1999). Dahası, bir kamu sektörünün örgüt kültürü özel sektörün örgüt kültürüne göre daha geniş ölçekli ve bilişsel yönü ağır basar.…”
Section: Introductionunclassified